Cerebral Palsy - Current Steps 2016
DOI: 10.5772/64638
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training in People with Cerebral Palsy

Abstract: Disorders affecting muscle strength in children with cerebral palsy (CP) are indicated among the main reasons of the motor performance disorder. Muscle weakness is a common disorder in children with CP and is associated with insufficient or reduced motor unit discharge, inadequate coactivation of antagonist muscles, secondary myopathy, and impaired muscle physiology. Studies have shown the usefulness of strength training in children with CP and revealed the relationship of muscle strength with activity. Streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
(172 reference statements)
0
3
0
Order By: Relevance
“…The muscles of children with CP have an increased amount of collagen, which hinders movement. This increase in collagen is responsible for contracture development, thereby affecting the passive viscoelastic features of muscle and exerting an impact on the internal resistance of muscle when passive movement of the joint is performed [ 16 ]. A weak agonist muscle may not allow full lengthening of the spastic antagonist muscle, leading to contracture development, and an increase in passive tension leads to muscle weakness [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The muscles of children with CP have an increased amount of collagen, which hinders movement. This increase in collagen is responsible for contracture development, thereby affecting the passive viscoelastic features of muscle and exerting an impact on the internal resistance of muscle when passive movement of the joint is performed [ 16 ]. A weak agonist muscle may not allow full lengthening of the spastic antagonist muscle, leading to contracture development, and an increase in passive tension leads to muscle weakness [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient tonus of the internal intercostal muscles, oblique abdominal muscles, and the diaphragm fibres (sternal part) lower the sternum at inspiration. This, in turn, together with insufficient chest decompression, flattens breathing, increases the breathing rate, reduces ventilatory capacity, and leads to abnormal chest wall development [14].…”
Section: Discussionmentioning
confidence: 99%
“…The impairment in strength in children with CP can be due to both the disturbed neural mechanisms and the muscle tissue changes. In children with CP, the central input that stimulates the motor neurons of the muscles is decreased due to pyramidal tract damage, also the child is unable to activate the high-threshold motor unit groups necessary for maximum voluntary contraction [27]. Modlesky and Zhang [28] suggested that CP have smaller muscles that contain less contractile tissue and more fat, which interfere with force generation and contribute to significant muscle weakness.…”
Section: Discussionmentioning
confidence: 99%